Prognostic Value of ECG in Patients with Pulmonary Embolism - I. S. Mullova; T. V. Pavlova; S. M. Khokhlunov; D. V. Duplyakov (Столичная издательская компания, 2019)
Aim. To study the significance of electrocardiography (ECG) signs for determining the hospital prognosis in patients with pulmonary embolism (PE).Material and methods. 472 consecutive patients (49.6% men; average age 58.06±14.28 years) with PE, hospitalized to our center from 23.04.2003 to 18.09.2014 were enrolled into the study. In all cases PE was confirmed by computed tomographic pulmonary angiography and rarely by pulmonary angiography, or by pathology. Patients management was in accordance with appropriate European guidelines. Data of patients' history, clinical symptoms, biochemical markers and instrumental methods (ECG, echocardiography) were analyzed by one-dimensional logistic regression. The end points were: death, shock and hypotension, right ventricular dysfunction and pulmonary hypertension, positive cardiac biomarkers.pulmonary embolism, electrocardiography, prognosis, collapse, hypotension, dysfunction of the right ventricle. 443 patients (93.9%) without fatal outcome were the first group and 29 patients (6.1%) with a fatal outcome - the second group. SIQIII pattern (33 vs 55.2%; p=0.015), non-complete right bundle branch block (RBBB) (16.3 vs 37.9%; p=0.001), ST segment elevation in lead III (9.7 vs 20.7%, p=0.034), atrial fibrillation (12.9 vs 37.9%, p=0.048) were observed more frequently among patients of group 2. Multivariate analysis revealed that SIQIII pattern (odds ratio [OR] 2.26; 95% confidence interval [95%CI] 1.046-4.868; p=0.038) and RBBB (OR 2.84; 95%CI 1.272-6.327; p=0.011) were associated with worse prognosis. The SIQIII pattern was significantly associated with a fatal outcome with a sensitivity of 55% and a specificity of 33% (AUC=0.611) according to ROC-analysis. Risk of hypotension was related to the following ECG-signs: the p-pulmonale (OR 1.76; 95%CI 1.001-3.088; p=0.049), negative T-wave in lead III (OR 1.8; 95%CI 1.035-3.144; p=0.037). Inversion of the T wave in lead III was associated with the development of shock (OR 1.98; 95%CI 0.891-4.430; p=0.043).ECG-signs were also associated with the development of right ventricular dysfunction and pulmonary hypertension: right axis deviation (OR 1.035; 95%CI 1.008-1.062; p=0.01), ST-segment elevation in the AVR lead (OR 3.769; 95%CI 1.018-13.955; p=0.047), negative T wave in leads III, V1-V3 (OR 1.015; 95%CI 1.008-1.023; p=0.001 and OR 1.014; 95%CI 1.005-1.022; p=0.001, respectively), RBBB (OR 1.013; 95%CI 1.003- 1.024; p=0.012), p-pulmonale (OR 1.015; 95%CI 1.007-1.023; p=0.001), deep S in leads V5-V6 (OR 1.015; 95%CI 1.006-1.024; p=0.001). However, there was no significant relationship between ECG signs and cardiac biomarkers (troponin I and BNP).Conclusions. SIQIII pattern, RBBB and inversion of the T wave in lead III have prognostic value in unselected population of patients with PE.